Plankton Diversity in Karst River, Masigit - Pawon Cave, West Java, Indonesia - Muhammad Wahyudin Lewaru; Fifi Dwi Pratiwi; Sunardi Sunardi (Journal Omni-Akuatika, 2019)
Karst Citatah region has been known strategies economic value of biotic and a biotic resources. This study investigated plankton biodiversity potency on Cibukur and Cibodas rivers where it already made in Karst Citatah region, particularly on Masigit-Pawon. The result of four stations showed that Karst Masigit-Pawon region was high potency with Plankton biodiversity resources with Diversity and dominancy index almost 1. The numbers of Plankton identified were of 24 species of phytoplankton consist of 9 class and 16 species of zooplankton consists of 6 filum. The high abundance of Plankton was Navicula sp(5.280 species), Synedra sp(4.092 species), dan Cyclops sp(2.904 species) respectively.